Structure of Ukrainian Agricultural Insurance Market in Terms of Sectoral Gradation - Olena PROKOPCHUK; Olena NEPOCHATENKO; Mykhaylo MALYOVANYI; Svitlana VLASYUK; Nataliia IVANOVA (Communications of International Proceedings, 2020)
The article investigates the internal structure features of the agricultural insurance market, which resulted in III sectors gradation; each of them forms separate structural elements or their totality. It is determined that the authorized body for supervision of insurance activity (State Financial Services Commission) belongs to the sector I of the internal structure of agricultural insurance market; to sector II - structural elements; to sector III - elements of infrastructure. The external environment of the agricultural insurance market is a system of interrelated factors that surround and affect its internal system. This classification makes it possible to describe the structure of the agricultural insurance market as a complex polystructural system having a three-sector internal structure and surrounded by the external environment and to substantiate the feasibility of complex supervision, regulation and development of all its constituent elements. The essence of the concept of “agricultural insurance market” is investigated and the author's definition is presented.
Keywords: Agricultural Insurance Market; Internal Structure; Regulator Of The Agricultural Insurance Market; Structural Elements; Infrastructure Elements.